Perkembangan Hukum Gadai Islam Dari Nash Syariah Menuju Qanun Sebagai Regulasi Formal Negara - Yusuf Yusuf; Oyo Sunaryo Mukhlas; Atang Abdul Hakim (STAI Al-Mas'udiyah, 2025)
The main purpose of this study is to examine the development of the concept of pawn (rahn) in Islam, starting from normative sources in the form of nash (Qur'an and Hadith), the thoughts of scholars in classical fiqh literature, to its implementation in the form of modern laws and regulations or known as qanun. The method used in this study is a qualitative method with a descriptive-analytical approach. Data was collected through library research, by examining various primary sources such as the Qur'an, Hadith, and jurisprudence, as well as secondary sources in the form of books, journals, and related legal documents. The results of the study show that the basic principles of pawn in nash, such as justice, help-help, and the prohibition of usury, are still used as the basis in the preparation of qanun. However, there have been administrative and technical adjustments to adapt to the needs of the positive law and contemporary institutional system. Qanun as a codification of Islamic law in Indonesia is able to accommodate sharia values in the practice of pawning in a more systematic and professional manner. Thus, despite changes in form and management, the substance of rahn in Islam is maintained from nash to qanun.